INVESTIGATING AND CORRELATING STUDENTS’ PERCEPTIONS, INTERESTS, AND ATTITUDES TOWARD THE IMPLEMENTATION OF PROJECT-BASED LEARNING THROUGH YOUTUBE VIDEO PROJECT IN LEARNING ENGLISH - Bidzlamira Dita Centrisia; Khoirul Anwar; Nirwanto Maruf (University of Kuningan, 2025)
Abstract - This study aims to examine and correlate students’ perceptions, interests, and attitudes toward implementing Project-Based Learning (PjBL) through YouTube video projects in English language learning. Using a mixed-methods design, this study combined quantitative data from questionnaires with qualitative data from semi-structured interviews. Participants consisted of 70 eleventh-grade students from SMAN 1 Pacitan who had been involved in YouTube-based PjBL activities during English language teaching. The questionnaire was designed to assess three main constructs: perceptions (cognitive, affective, conative), interests (individual, situational, topic-based), and attitudes (cognitive, affective, behavioral). Prior to data analysis, the instrument was subjected to validity and reliability tests. All items were deemed valid based on the item-total correlation value, and the reliability analysis yielded a Cronbach’s Alpha coefficient of 0.976, indicating excellent internal consistency. The findings revealed that students generally responded positively to the integration of YouTube-based PjBL, considering it an innovative and engaging approach that increased their motivation and participation in English language learning. Students also reported increased interest, particularly in producing creative content and collaborating with peers. Attitudinal responses indicated greater confidence, enjoyment, and willingness to communicate in English. Overall, the implementation of YouTube video projects within a PjBL framework proved effective in fostering a more dynamic and student-centered English learning environment. The study suggests that the integration of digital media, when aligned with project-based methodologies, has significant potential to enrich language teaching and enhance 21st century skills.